GARP as a Therapeutic Target for the Modulation of Regulatory T Cells in Cancer and Autoimmunity - Zimmer, Niklas; Trzeciak, Emily R.; Graefen, Barbara; Satoh, Kazuki; Tuettenberg, Andrea (Frontiers in Immunology, 2022)
Regulatory T cells (Treg) play a critical role in immune homeostasis by suppressing several aspects of the immune response. Herein, Glycoprotein A repetitions predominant (GARP), the docking receptor for latent transforming growth factor (LTGF-β), which promotes its activation, plays a crucial role in maintaining Treg mediated immune tolerance. After activation, Treg uniquely express GARP on their surface. Due to its location and function, GARP may represent an important target for immunotherapeutic approaches, including the inhibition of Treg suppression in cancer or the enhancement of suppression in autoimmunity. In the present review, we will clarify the cellular and molecular regulation of GARP expression not only in human Treg but also in other cells present in the tumor microenvironment. We will also examine the overall roles of GARP in the regulation of the immune system. Furthermore, we will explore potential applications of GARP as a predictive and therapeutic biomarker as well as the targeting of GARP itself in immunotherapeutic approaches